Evaluating the Stability and Adequacy of NIGNET for the Definition of Nigerian Geodetic Reference Frame - E. Ayodele (Nigerian Journal of Technological Development, 2020)
A set of Continuously Operating Reference Stations (CORS) distributed all over Nigeria constitutes the Nigerian GNSS Reference Network referred to as NIGNET. Global Navigation Satellite System (GNSS) is a system that uses satellites for autonomous position determination, and is a critical component of the modern-day geodetic infrastructure and services. Using CORS provide geodetic controls of comparable accuracy and a better alternative to the classical geodetic network. As the NIGNET infrastructure is utilised for different geodetic applications, it has become necessary to evaluate the suitability of the network data for the definition of a geodetic reference frame (GRF). This study utilised the technique of Precise Point Positioning (PPP) in position estimation, and time series analysis for temporal monitoring of the network. The sufficiency and adequacy of the NIGNET data archive was also evaluated against that of an International GNSS Service (IGS) Station. The temporal stability of the station coordinates measured in terms of standard deviations varied between 10 mm and 22 mm. This analysis suggests a relative stability required for Tiers 1 and 2 CORS in line with the IGS standards. Based on this reported stability, it is concluded that NIGNET is fit for purpose in defining the Nigerian Geodetic Reference Frame. However, despite the good data quality observed, the adequacy of the network has been compromised by infrastructural failures and lack of continuity in data transmission. Accordingly, it is recommended that both practical and policy measures required to ensure the realisation of the goal of the network should be implemented.